EFISIENSI TEKNIS USAHATANI PADI TADAH HUJAN DI KAWASAN PERBATASAN KABUPATEN SAMBAS DENGAN PENDEKATAN STOCHASTIC FRONTIER FUNGSI PRODUKSI (KASUS DI DESA SEBUBUS, KECAMATAN PALOH) - Burhansyah, Rusli (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Development of rice for food self-sufficiency in the border region of Sambas regency is quite prospective. However, in the District Paloh rice productivity is still relatively low, allegedly due to inefficiency in the use of inputs. The aim of this study was to analyze the efficiency and income of rice farming in the village of Sebubus, Paloh district. The research method used was stohastic frontier of production function with OLS and Maximum likelihood (MLE). The study was conducted in the village Sebubus, District Paloh between May - June 2014. Sampling was done with Proportionate Stratified Random Sampling. The data used was the cross section data obtained from interviews of 120 rice farmers. The Stohastic frontier of production function analysis was performed using the Cobb-Douglas models. The results showed that land, N fertilizer and K fertilizer significantly affected rice production at 95% confidence level. The results also showed that rainfed rice paddy was relatively efficient technically (mean efficiency of 0,81). Age of farmers was a source of technical inefficiency that significantly could improve technical efficiency. Characteristics of farmers such as age, education and experience could help farmers improve their technical efficiency of rice production. Rainfed rice farming in the village Sebubus was relatively favorable (profit of USD 4,099,582.50) and viable (the value of R/C ratio above 2,84 cash costs and the value of R/C ratio on total cost of 2,29).